Understanding the connection: attachment patterns and interpersonal competence in nursing undergraduates - Mona Metwally El-Sayed; Samah Mohamed Taha; Eman Sameh AbdElhay; Bothaina Hussein Hassan; Helalia Shalabi Mohamed Shalabi; Mahmoud Abdelwahab Khedr (BMC Nursing)
Abstract Background Interpersonal skills are vital in nursing and influence patient care and teamwork. Attachment patterns strongly affect these skills, with secure attachments fostering empathy and effective communication. Aim This study examined the relationships between attachment patterns (secure, anxious, avoidant) and interpersonal competencies among nursing students. Methods A cross-sectional self-report questionnaire, which included data from 426 undergraduate nursing students, was collected at Mansoura University in Egypt. Sociodemographic information, the Revised Adult Attachment Scale (RAAS), and the Social and Emotional Competencies Questionnaire (SEC-Q) were used for data collection. Results Secure attachment was positively associated with self-awareness (r = 0.201, p ≤ 0.01), social awareness (r = 0.202, p ≤ 0.01), and the total SEC-Q score (r = 0.210, p ≤ 0.01). In contrast, dependent attachment exhibited a weak negative correlation with social awareness (r = -0.134, p ≤ 0.05), whereas anxious attachment was negatively correlated with decision-making (r = -0.144, p ≤ 0.05). Regression analysis revealed that attachment patterns significantly predicted social-emotional competency (F = 169.782, p < 0.001, R² = 0.168), accounting for 16.2% of the variance in the SEC-Q scores. Secure attachment positively predicted competency (B = 0.071, Beta = 0.191, t = 2.750, p = 0.006), whereas dependent attachment negatively predicted it (B = -0.100, Beta = -0.193, t = -2.775, p = 0.006). Anxious attachment had no significant effect (B = -0.209, Beta = -0.030, t = -0.419, p = 0.676). The Pearson correlation coefficient, multiple linear regression analysis, and mean and standard deviation were employed for statistical analysis. Conclusion Nurturing secure attachment in nursing education can enhance students’ interpersonal competencies, ultimately improving patient care and team dynamics. Addressing attachment-related challenges helps foster emotional intelligence, benefiting both students and future patients. Clinical trial number Not applicable.